2018
DOI: 10.4103/ipj.ipj_27_18
|View full text |Cite
|
Sign up to set email alerts
|

To identify predictors of relapse in cases of alcohol dependence syndrome in relation to life events

Abstract: Background and Objectives:Relapse is a complex and dynamic phenomenon that appears to be determined by biological, psychological, and social factors and an interaction among these. This study examined the association between demographic variables, clinical parameters, and psychosocial factors that predict the vulnerability to relapse in cases of alcohol dependence syndrome.Materials and Methods:Structured assessments of clinical/demographic parameters, relapse precipitants, life events, and dysfunction were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
5
12
0
Order By: Relevance
“…It was also observed that 77.3% of participants had a family member who also drank alcohol. This finding was congruent with other studies that indicated a positive history of alcohol use among people with alcohol relapse [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…It was also observed that 77.3% of participants had a family member who also drank alcohol. This finding was congruent with other studies that indicated a positive history of alcohol use among people with alcohol relapse [42, 43].…”
Section: Discussionsupporting
confidence: 93%
“…When the participants spoke of the causes for relapsing, it became apparent that their mental distress was associated with their relapses. They explained that relapses had been accompanied by a great deal of negative emotions, and it was evident that some of the participants felt they had failed their relatives and themselves, which is in accordance with findings from previous studies ( Chauhan et al, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…Few other studies showed higher relapse. 7,10,12 In the current study the, the univariate analysis had shown age at first drink in years, total duration of drinking in months and use of disulfiram and graduation as educational status are associated with higher odds of relapse. Having financial debts, prescription antidepressant intake and RTA under intoxication were associated with lower odds of relapse among the study population.…”
Section: Discussionmentioning
confidence: 46%
“…9 Therefore, relapse as a central issue in the treatment of alcohol dependence warrants further study. 10 Hence, in this study the factors associated with abstinence, lapse and relapse of drinking after an in-patient deaddiction programme was investigated. The current study showed that only 22(31.43%) participant were abstinent meaning most patient either had a lapse or a relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation